2021
DOI: 10.1109/access.2021.3104717
|View full text |Cite
|
Sign up to set email alerts
|

Model-Based Approach for Assessing Planning Quality in Production Logistics

Abstract: Funded by Deutsche Forschungsgemeinschaft (DFG, German Research Foundation) "SFB 871/3" -119193472 and "Systematic analysis of the effect of production planning and control processes on logistical objectives" -434659386.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…Manufacturing area in recent years is still amongst the most impacted fields by advances of DA and digital transformation, which resulted in huge expansion of data availability (Tamás & Koltai, 2020). Production planning and control are the dominant topics for applying DA in this context (Lucht et al, 2021). The results of the current literature review are in line with the previous one and we also confirmed that most papers in the manufacturing area address production planning and control issues.…”
Section: In What Areas Of Scm Is Da Being Applied?supporting
confidence: 86%
“…Manufacturing area in recent years is still amongst the most impacted fields by advances of DA and digital transformation, which resulted in huge expansion of data availability (Tamás & Koltai, 2020). Production planning and control are the dominant topics for applying DA in this context (Lucht et al, 2021). The results of the current literature review are in line with the previous one and we also confirmed that most papers in the manufacturing area address production planning and control issues.…”
Section: In What Areas Of Scm Is Da Being Applied?supporting
confidence: 86%
“…Planning quality is a commonly used term to indicate how good production planning is [26]. Planning quality can be understood as a key indicator for the planner to assess the reliability of the production plan in the planning phase and to continuously improve the operational reliability of production plans in forthcoming phases [27,28].…”
Section: Planning Qualitymentioning
confidence: 99%
“…The deviations can be caused by uncertainties such as inaccurate or incomplete planning data, unforeseeable external events, or inappropriate PPC systems. Planning quality can also be assessed with regards to planning accuracy and plan stability [26].…”
Section: Planning Qualitymentioning
confidence: 99%
“…Therefore, it is increasingly difficult to identify and solve the inefficiency or other problems induced by the planning process of the industrial supply chain. Lucht et al [27] proposed a convenient way to describe, visualize, and analyze the scheduling behavior of manufacturing enterprises with very few data, summarized the key evaluation indices of planning quality, and constructed an evaluation model covering two dimensions: planning stability, and planning accuracy.…”
Section: Introductionmentioning
confidence: 99%